Álgebra linear: uma conexão do ensino médio ao superior - Vieira, Halisson Barreto (2013)
This work is a study of linear systems from the perspective of linear algebra. We will use the concepts of matrix, vector, linear combination, linear dependence and independence, vector space, basis and dimension. We will also calculate the determinants and implications. Our aim is to present the rudiments of Linear Algebra as helper tool in solving linear systems and display its geometry. We want it to manufacture a auxiliary text that can be explored by students and high school teachers, and so gently introducing this powerful mathematical tool. Throughout the text will be covered also some historical aspects.